Laminated materials and packaging materials for liquid packaging

By adopting a multi-layer film structure of vinyl heat sealing layer and extended polyethylene film in the packaging material, combining polylactic acid polyisomer acid polylactic acid coating and curable adhesive layer, the problems of poor recycling performance and poor fragrance retention are solved, and high recycling performance and strong heat sealing strength are achieved.

JP7648018B2Active Publication Date: 2025-03-18DIC CORP
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2024564731
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-12-22
Filing Date
2023-12-14
Publication Date
2025-03-18
Estimated Expiration
2043-12-14

AI Technical Summary

Technical Problem

The recycling performance of existing packaging materials is poor, especially the difficulty in separation of different types of resins in multi-layer films, and low-polar films such as paraffin films have poor performance in fragrance retention, making them unable to be suitable for packaging products containing fragrances.

Method used

A multi-layer film structure containing a vinyl heat sealing layer is adopted, which includes an extended polyethylene film, a vinyl heat sealing layer, a coating and polylactic acid polyisomeric acid polylactic acid as coating components, and two parts of a curable adhesive layer are added between the extended polyethylene film and the vinyl heat sealing layer to improve fragrance retention and heat sealing strength.

Benefits of technology

It achieves high recycling performance of packaging materials, good fragrance retention and strong heat seal strength, making them suitable for liquid packaging materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007648018000001
    Figure 0007648018000001
Patent Text Reader

Abstract

The present invention provides: a multilayer body which has excellent recyclability, aroma retention properties and heat seal strength, while being suitable for liquid packaging materials; and a liquid packaging material. The present invention provides a multilayer body for liquid packaging materials, the multilayer body comprising a stretched polyethylene film, an ethylene-based heat seal layer that has a film thickness of 45 µm to 250 µm, a coat layer that is disposed between the stretched polyethylene film and the heat seal layer, and an adhesion layer that is disposed between the stretched polyethylene film and the ethylene-based heat seal layer, wherein: the coat layer is a cured coating film of a coating agent which contains a polyisocyanate and a polyester polyol that comprises a skeleton derived from an ortho-directing aromatic carboxylic acid; and the adhesive layer is a cured coating film of a coating agent which contains a polyisocyanate and a polyester polyol that comprises a skeleton derived from an ortho-directing aromatic carboxylic acid.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a laminate having excellent aroma retention properties and suitable for use as a liquid packaging material, and to a packaging material using the laminate. [Background technology]

[0002] Packaging materials used for packaging food and daily necessities are usually made of a laminate in which a heat-sealable film such as a polyethylene film or a polypropylene film is bonded to a resin film having excellent heat resistance and strength such as a polyester film or a nylon film using an adhesive (Patent Documents 1 and 2). Meanwhile, in recent years, with the growing demand for the creation of a recycling-oriented society, attempts have been made to recycle and reuse packaging materials. However, in laminates in which different types of resin films are bonded together as described above, it is difficult to separate the resins by type, and they are not suitable for recycling. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2014-004799 A [Patent Document 2] JP 2004-238050 A Summary of the Invention [Problem to be solved by the invention]

[0004] A laminate for packaging with excellent recyclability can be made by using a biaxially oriented polyolefin film such as oriented polypropylene or oriented polyethylene film on the outer layer side from the content side, and an unoriented polypropylene film or low-density polyethylene film on the inner layer side (sealant film). Since most of the laminate is made up of olefin resin, such laminates have excellent recyclability compared to laminates using different types of substrates, but laminates made by bonding low-polarity films such as olefin-based films have significantly inferior aroma retention compared to laminates using polar films such as PET films. They are not suitable for packaging products that contain fragrances, such as shampoos, conditioners, and dishwashing detergents.

[0005] Furthermore, when most of the laminate is made of olefin resin, the heat resistance of the laminate is low, so the heat sealing cannot be performed at a high temperature and the heat sealing time must be short. As a result, the heat seal strength tends to be low, making it unsuitable for packaging liquid products such as shampoo, conditioner, and dishwashing detergent.

[0006] The present invention has been made in view of the above circumstances, and an object of the present invention is to provide a laminate and a liquid packaging material which are excellent in recyclability, aroma retention and heat seal strength and are suitable for use as liquid packaging materials. [Means for solving the problem]

[0007] The present invention relates to a laminate for liquid packaging, comprising a stretched polyethylene film, an ethylene-based heat seal layer having a thickness of 45 μm or more and 250 μm or less, a coating layer disposed between the stretched polyethylene film and the heat seal layer, and an adhesive layer disposed between the stretched polyethylene film and the ethylene-based heat seal layer, wherein the coating layer is a cured coating film of a coating agent containing a polyester polyol having a skeleton derived from an ortho-oriented aromatic carboxylic acid and a polyisocyanate, and the adhesive layer is a cured coating film of a coating agent containing a polyester polyol having a skeleton derived from an ortho-oriented aromatic carboxylic acid and a polyisocyanate, and a liquid packaging material obtained using the same. Effect of the Invention

[0008] According to the laminate of the present invention, it is possible to obtain a laminate and a packaging material which are highly recyclable and suitable for packaging liquid packages. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Laminate> (Stretched polyethylene film) Examples of the oriented polyolefin film include a high density polyethylene film (HDPE), a uniaxially oriented polyethylene film (MDOPE), and a biaxially oriented polyethylene film (BOPE).

[0010] The stretched polyethylene film may contain additives as necessary. Specifically, plastic compounding agents and additives such as lubricants, crosslinking agents, antioxidants, UV absorbers, light stabilizers, fillers, reinforcing agents, antistatic agents, and pigments may be added for the purpose of improving or modifying processability, heat resistance, weather resistance, mechanical properties, dimensional stability, oxidation resistance, slipperiness, mold releasability, flame retardancy, mold resistance, electrical properties, strength, etc. The amount of additives added is adjusted within a range that does not affect other properties.

[0011] The stretched polyethylene film may be subjected to a surface treatment, which can improve the adhesion between adjacent layers. The method of the surface treatment is not particularly limited, and examples thereof include physical treatments such as corona discharge treatment, ozone treatment, low-temperature plasma treatment using oxygen gas and / or nitrogen gas, and glow discharge treatment, as well as chemical treatments such as oxidation treatment using chemicals.

[0012] The thickness of the stretched polyethylene film can be adjusted appropriately depending on the purpose, but in terms of the balance between mechanical strength and processability, it is preferably 7 μm to 300 μm, and more preferably 15 μm to 100 μm.

[0013] (Ethylene-based heat seal layer) The ethylene-based heat seal layer is made of an ethylene-based resin and has a heat sealability of melting and fusing with each other by heat. Specific examples include polyethylene resins such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), very low-density polyethylene (VLDPE), and ethylene-propylene copolymers, ethylene-vinyl acetate copolymers (EVA), ethylene-methyl methacrylate copolymers (EMMA), ethylene-ethyl acrylate copolymers (EEA), ethylene-methyl acrylate (EMA) copolymers, ethylene-ethyl acrylate-maleic anhydride copolymers (E-EA-MAH), ethylene-acrylic acid copolymers (EAA), and ethylene-methacrylic acid copolymers (EMAA), and further ionomers of ethylene-acrylic acid copolymers, ionomers of ethylene-methacrylic acid copolymers, and the like, which may be used alone or in combination of two or more kinds.

[0014] Among these, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and very low-density polyethylene (VLDPE) ethylene-propylene copolymers are preferably used because they can easily ensure suitable heat sealability even when thin, have high adhesion to other resin layers such as the first cyclic polyolefin resin layer described below, and easily improve film formation stability when co-extruded with said layer, with linear low-density polyethylene (LLDPE) and ethylene-propylene copolymers being particularly preferred.

[0015] The LDPE may be any branched low-density polyethylene obtained by high-pressure radical polymerization, and is preferably a branched low-density polyethylene obtained by homopolymerizing ethylene by high-pressure radical polymerization.

[0016] As the LLDPE, a copolymer of ethylene monomer as the main component and α-olefin such as butene-1, hexene-1, octene-1, 4-methylpentene, etc. as a comonomer by low pressure radical polymerization method using a single site catalyst can be preferably used. The comonomer content in the LLDPE is preferably in the range of 0.5 to 20 mol%, more preferably in the range of 1 to 18 mol%.

[0017] Examples of single-site catalysts include various single-site catalysts such as metallocene catalyst systems, such as combinations of metallocene compounds of transition metals of Group IV or V of the periodic table with organoaluminum compounds and / or ionic compounds. Single-site catalysts have uniform active sites, and therefore, compared with multi-site catalysts, which have non-uniform active sites, the molecular weight distribution of the resulting resin is sharper, and thus low-molecular-weight components are less likely to precipitate when the catalyst is formed into a film, and a resin with excellent physical properties such as stable seal strength and excellent blocking resistance is obtained, which is preferable.

[0018] The density of ethylene resin is 0.880 to 0.970 g / cm 3 It is preferable that the density is within this range. If the density is within this range, the film has appropriate rigidity, and mechanical strength such as heat seal strength and pinhole resistance is excellent, and the film formability and extrusion suitability are improved. In addition, the melting point is generally preferably within the range of 60 to 130°C, more preferably 70 to 120°C. If the melting point is within this range, the processing stability and co-extrusion processability with the first cyclic polyolefin resin layer described below are improved. Furthermore, since the film has flexibility, the pinhole resistance is also good. In addition, the MFR (190°C, 21.18N) of the ethylene resin is preferably 2 to 20g / 10min, more preferably 3 to 10g / 10min. If the MFR is within this range, the extrusion moldability of the film is improved.

[0019] The thickness of the ethylene-based heat seal layer is 45 μm or more and 250 μm or less. This allows a laminate with excellent heat seal strength and content resistance to be obtained. The thickness of the ethylene-based heat seal layer is more preferably 60 μm or more, 70 μm or more, and 230 μm or less, and 210 μm or less.

[0020] (adhesive layer) The adhesive layer is a cured coating of a two-component curing adhesive, and is disposed between the stretched polyethylene film and the ethylene-based heat seal layer. The two-component curing adhesive used in the present invention contains a polyol composition (X1) containing a polyester polyol (A) and a polyisocyanate composition (Y1) containing a polyisocyanate (B).

[0021] The polyester polyol (A) is a reaction product of a monomer composition (A') containing a polycarboxylic acid and a polyhydric alcohol, and includes at least one of a polyester polyol (A1) obtained by polycondensation of a polycarboxylic acid including an ortho-oriented aromatic polycarboxylic acid with a polyhydric alcohol, a polyester polyol (A2) having an isocyanuric ring, and a polyester polyol (A3) having a polymerizable carbon-carbon double bond.

[0022] Examples of ortho-oriented polyvalent carboxylic acids used in the synthesis of polyester polyol (A1) include orthophthalic acid or its anhydride, naphthalene 2,3-dicarboxylic acid or its anhydride, naphthalene 1,2-dicarboxylic acid or its anhydride, anthraquinone 2,3-dicarboxylic acid or its anhydride, and 2,3-anthracene carboxylic acid or its anhydride. These compounds may have a substituent on any carbon atom of the aromatic ring. Examples of the substituent include a chloro group, a bromo group, a methyl group, an ethyl group, an i-propyl group, a hydroxyl group, a methoxy group, an ethoxy group, a phenoxy group, a methylthio group, a phenylthio group, a cyano group, a nitro group, an amino group, a phthalimide group, a carboxyl group, a carbamoyl group, an N-ethylcarbamoyl group, a phenyl group, or a naphthyl group.

[0023] The polybasic carboxylic acid used in the synthesis of the polyester polyol (A1) may contain a polybasic carboxylic acid other than the ortho-oriented polybasic carboxylic acid. Examples of polycarboxylic acids other than the ortho-oriented polycarboxylic acid include aliphatic polycarboxylic acids such as succinic acid, adipic acid, azelaic acid, sebacic acid, and dodecanedicarboxylic acid; unsaturated bond-containing polycarboxylic acids such as maleic anhydride, maleic acid, and fumaric acid; alicyclic polycarboxylic acids such as 1,3-cyclopentanedicarboxylic acid and 1,4-cyclohexanedicarboxylic acid; terephthalic acid, isophthalic acid, pyromellitic acid, trimellitic acid, 1,4-naphthalenedicarboxylic acid, 2,5-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, naphthalic acid, biphenyldicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p'-dicarboxylic acid, and anhydrides or ester-forming derivatives of these dicarboxylic acids; aromatic polycarboxylic acids such as p-hydroxybenzoic acid, p-(2-hydroxyethoxy)benzoic acid, and ester-forming derivatives of these dihydroxycarboxylic acids; and the like. One or more of these may be used in combination. Among these, succinic acid, 1,3-cyclopentanedicarboxylic acid, isophthalic acid and acid anhydrides thereof are preferred.

[0024] When the polycarboxylic acid contains a polycarboxylic acid other than an ortho-oriented polycarboxylic acid, the proportion of the ortho-oriented polycarboxylic acid in the total amount of the polycarboxylic acid is preferably 50 to 100% by mass.

[0025] The polyhydric alcohol used in the synthesis of polyester polyol (A1) preferably contains at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, glycerin, trimethylolethane, trimethylolpropane, and cyclohexanedimethanol, and more preferably contains at least one selected from ethylene glycol and glycerin. The amount of these polyhydric alcohols in the polyhydric alcohols that are the raw materials for polyester polyol (A1) is preferably 20 mass% or more. The total amount may be these polyhydric alcohols.

[0026] The polyhydric alcohol may be used in combination with a polyhydric alcohol other than those mentioned above. Examples of the polyhydric alcohol include aliphatic diols such as 1,5-pentanediol, 3-methyl-1,5-pentanediol, 1,6-hexanediol, methylpentanediol, dimethylbutanediol, butylethylpropanediol, diethylene glycol, triethylene glycol, tetraethylene glycol, dipropylene glycol, and tripropylene glycol; trihydric or higher polyhydric alcohols such as tris(2-hydroxyethyl)isocyanurate, 1,2,4-butanetriol, pentaerythritol, and dipentaerythritol; hydroquinone, resorcinol, catechol, naphthalenediol, biphenol, bisphenol A, hisphenol F, and tetramethylbiphenol; ethylene oxide-extended products of these; and aromatic polyhydric phenols such as hydrogenated alicyclic alcohols.

[0027] When the polyester polyol (A1) has three or more hydroxyl groups (for convenience, referred to as polyester polyol (a1)), some of the hydroxyl groups may be modified with an acid group. Such a polyester polyol is also referred to as polyester polyol (A1') below. The polyester polyol (A1') is obtained by reacting the polyester polyol (a1) with a polycarboxylic acid or its acid anhydride. The ratio of the hydroxyl groups modified with the polycarboxylic acid is preferably 1 / 3 or less of the hydroxyl groups of the polyester polyol (a1). Examples of the polycarboxylic acid used for modification include, but are not limited to, succinic anhydride, maleic acid, maleic anhydride, fumaric acid, 1,2-cyclohexane dicarboxylic anhydride, 4-cyclohexene-1,2-dicarboxylic anhydride, 5-norbornene-2,3-dicarboxylic anhydride, phthalic anhydride, 2,3-naphthalenedicarboxylic anhydride, trimellitic anhydride, oleic acid, and sorbic acid.

[0028] The polyester polyol (A2) is obtained, for example, by reacting a triol having an isocyanuric ring with a polycarboxylic acid including an ortho-oriented aromatic polycarboxylic acid and a polyhydric alcohol. Examples of the triol having an isocyanuric ring include alkylene oxide adducts of isocyanuric acid such as 1,3,5-tris(2-hydroxyethyl)isocyanuric acid and 1,3,5-tris(2-hydroxypropyl)isocyanuric acid. The ortho-oriented aromatic polycarboxylic acid, polycarboxylic acid, and polyhydric alcohol can be the same as those used for the polyester polyol (A1).

[0029] As the triol compound having an isocyanuric ring, it is preferable to use 1,3,5-tris(2-hydroxyethyl)isocyanuric acid or 1,3,5-tris(2-hydroxypropyl)isocyanuric acid. As the ortho-oriented aromatic polycarboxylic acid, it is preferable to use orthophthalic anhydride. As the polyhydric alcohol, it is preferable to use ethylene glycol.

[0030] The proportion of the triol having an isocyanuric ring in the polyhydric alcohol that is the raw material of the polyester polyol (A2) is preferably 10% by mass or more. There is no particular upper limit, but from the viewpoint of coating suitability, it is preferably 80% by mass or less.

[0031] The polyester polyol (A3) can be obtained by using a polyvalent carboxylic acid or a polyhydric alcohol having a polymerizable carbon-carbon double bond.

[0032] Examples of polyvalent carboxylic acids having a polymerizable carbon-carbon double bond include maleic anhydride, maleic acid, fumaric acid, 4-cyclohexene-1,2-dicarboxylic acid and its anhydride, 3-methyl-4-cyclohexene-1,2-dicarboxylic acid and its anhydride, etc. It is presumed that the molecular chain is less flexible and less permeable to oxygen as the number of carbon atoms decreases, so maleic anhydride, maleic acid, and fumaric acid are preferred. An example of a polyhydric alcohol having a polymerizable carbon-carbon double bond is 2-butene-1,4-diol.

[0033] In addition to the above, polyvalent carboxylic acids and polyhydric alcohols not having a polymerizable carbon-carbon double bond may be used in combination. As such polyvalent carboxylic acids and polyhydric alcohols, the same ones as those of the polyester polyols (A1) and (A2) can be used. As the polyvalent carboxylic acid, it is preferable to use at least one selected from the group consisting of succinic acid, 1,3-cyclopentanedicarboxylic acid, orthophthalic acid, orthophthalic acid anhydride, and isophthalic acid, and it is more preferable to use at least one orthophthalic acid and its acid anhydride. As the polyhydric alcohol, it is preferable to use at least one selected from the group consisting of ethylene glycol, propylene glycol, butylene glycol, neopentyl glycol, and cyclohexanedimethanol, and it is more preferable to use ethylene glycol.

[0034] The hydroxyl value of the polyester polyol (A) is preferably 1 mgKOH / g or more and 350 mgKOH / g or less. When the polyester polyol (A) has an acid group, the acid value is preferably 200 mgKOH / g or less. There is no particular restriction on the lower limit, but as an example, it is 0.5 mgKOH / g or more. It may be 0 mgKOH / g. The hydroxyl value of the polyester polyol (A) can be measured by the hydroxyl value measurement method described in JIS-K0070, and the acid value can be measured by the acid value measurement method described in JIS-K0070.

[0035] The number average molecular weight of the polyester polyol (A) is particularly preferably 300 to 5000, since a crosslinking density that provides an excellent balance between adhesion and aroma retention can be obtained. The number average molecular weight is more preferably 350 to 3000. The number average molecular weight is calculated from the obtained hydroxyl value and the number of functional groups of the designed hydroxyl group.

[0036] The glass transition temperature of the polyester polyol (A) is preferably from -30°C to 80°C, more preferably from 0°C to 60°C, and even more preferably from 25°C to 60°C, in view of the balance between adhesion to the substrate and aroma retention.

[0037] The polyester polyol (A) may be a polyester polyurethane polyol obtained by urethane elongation of a polyester polyol through a reaction with a diisocyanate compound to give a number average molecular weight of 1000 to 15000. The urethane-elongated polyester polyol contains a molecular weight component having a certain level or more and a urethane bond, and therefore has excellent initial cohesive strength and is excellent as an adhesive for lamination.

[0038] The polyisocyanate composition (Y1) contains an isocyanate compound (B). The isocyanate compound (B) may be any of the conventionally known compounds without any particular limitation. Examples of the isocyanate compound (B) include tetramethylene diisocyanate, hexamethylene diisocyanate, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, or trimers of these isocyanate compounds, and adducts obtained by reacting an excess amount of these isocyanate compounds with low molecular weight active hydrogen compounds such as ethylene glycol, propylene glycol, metaxylylene alcohol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, and metaxylylenediamine, and alkylene oxide adducts thereof, various polyester resins, polyether polyols, and polymeric active hydrogen compounds such as polyamides. A polyester polyisocyanate obtained by reacting at least one of the above-mentioned polyester polyols (A1) to (A3) with a diisocyanate compound in an isocyanate excess ratio between hydroxyl groups and isocyanate groups may be used. These may be used alone or in combination of two or more.

[0039] Also, blocked isocyanate may be used as the isocyanate compound. Examples of the isocyanate blocking agent include phenols such as phenol, thiophenol, methylthiophenol, ethylthiophenol, cresol, xylenol, resorcinol, nitrophenol, and chlorophenol, oximes such as acetoxime, methylethylketoxime, and cyclohexanoneoxime, alcohols such as methanol, ethanol, propanol, and butanol, halogen-substituted alcohols such as ethylene chlorohydrin and 1,3-dichloro-2-propanol, tertiary alcohols such as t-butanol and t-pentanol, lactams such as ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propylolactam, and also include aromatic amines, imides, active methylene compounds such as acetylacetone, acetoacetate, and malonic acid ethyl ester, mercaptans, imines, ureas, diaryl compounds, and sodium bisulfite. The blocked isocyanate can be obtained by subjecting the above-mentioned isocyanate compound to an addition reaction with an isocyanate blocking agent by a known, conventional, appropriate method.

[0040] Among these, it is more preferable to use isocyanate compounds having a skeleton derived from xylylene diisocyanate, hydrogenated xylylene diisocyanate, toluene diisocyanate, or diphenylmethane diisocyanate, since good aroma retention can be obtained.

[0041] Examples of such isocyanate compounds include a trimer of diisocyanate, a biuret compound synthesized by reaction with an amine, and an adduct compound formed by reaction with an alcohol. Compared with trimers and biuret compounds, adduct compounds have good solubility in organic solvents used in solvent-based adhesives, so that it is preferable to use an adduct compound when the adhesive is solvent-based. As the adduct compound, an adduct compound formed by reaction with an alcohol appropriately selected from the above low molecular weight active hydrogen compounds can be used, and among them, adduct compounds with an ethylene oxide adduct of trimethylolpropane, glycerol, triethanolamine, or metaxylenediamine are preferable.

[0042] In addition, when a composition containing a polyester polyol having residual carboxylic acid groups, such as polyester polyol (A1'), is used as the polyol composition (X1), the polyisocyanate composition (Y1) may contain an epoxy compound. Examples of the epoxy compound include diglycidyl ether of bisphenol A and its oligomer, diglycidyl ether of hydrogenated bisphenol A and its oligomer, orthophthalic acid diglycidyl ester, isophthalic acid diglycidyl ester, terephthalic acid diglycidyl ester, p-oxybenzoic acid diglycidyl ester, tetrahydrophthalic acid diglycidyl ester, hexahydrophthalic acid diglycidyl ester, succinic acid diglycidyl ester, adipic acid diglycidyl ester, sebacic acid diglycidyl ester, ethylene glycol diglycidyl ether, and propylene glycol diglycidyl. ether, 1,4-butanediol diglycidyl ether, 1,6-hexanediol diglycidyl ether, polyalkylene glycol diglycidyl ethers, trimellitic acid triglycidyl ester, triglycidyl isocyanurate, 1,4-diglycidyloxybenzene, diglycidyl propylene urea, glycerol triglycidyl ether, trimethylolethane triglycidyl ether, trimethylolpropane triglycidyl ether, pentaerythritol tetraglycidyl ether, triglycidyl ether of glycerol alkylene oxide adduct, and the like.

[0043] When an epoxy compound is used, a commonly known epoxy curing accelerator may be appropriately added for the purpose of accelerating curing within a range that does not impair the object of the present invention.

[0044] The polyol composition (X1) and the polyisocyanate composition (Y1) are preferably mixed so that the equivalent ratio of the hydroxyl group contained in the polyol composition (X1) to the isocyanate group contained in the polyisocyanate composition (Y1) is 1 / 0.5 to 1 / 10, and more preferably 1 / 1 to 1 / 5. If the isocyanate compound is excessive, the excess isocyanate compound remaining in the cured coating film of the adhesive may bleed out from the adhesive layer. On the other hand, if the reactive functional group contained in the polyisocyanate composition (Y1) is insufficient, the adhesive strength may be insufficient.

[0045] The adhesive may contain various additives (C) within the range that does not impair the effects of the present invention. As such additive (C), an inorganic filler (C1) may be used. Examples of the inorganic filler (C1) include silica, alumina, aluminum flakes, glass flakes, etc. In particular, it is preferable to use a plate-like inorganic compound as the inorganic filler (C1) because it improves adhesive strength, aroma retention, light-shielding properties, etc. Examples of the plate-like inorganic compounds include hydrated silicates (phyllosilicate minerals, etc.), kaolinite-serpentine clay minerals (halloysite, kaolinite, endelite, dickite, nacrite, etc., antigorite, chrysotile, etc.), pyrophyllite-talc (pyrophyllite, talc, keroli, etc.), smectite clay minerals (montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, etc.), vermiculite clay minerals (vermiculite, etc.), mica or mica clay minerals (muscovite, phlogopite, etc., mica, margarite, tetrasilylic mica, taeniolite, etc.), chlorite (cookite, sudoite, clinochlore, chamosite, nimite, etc.), hydrotalcite, plate-like barium sulfate, boehmite, aluminum polyphosphate, etc. These minerals may be natural clay minerals or synthetic clay minerals. The plate-like inorganic compounds can be used alone or in combination of two or more.

[0046] The plate-like inorganic compound may be ionic, having an electric charge between layers, or nonionic, having no electric charge. The presence or absence of an electric charge between layers does not directly affect the aroma retention of the adhesive layer. However, ionic plate-like inorganic compounds and inorganic compounds that swell in water are poorly dispersible in solvent-based adhesives, and increasing the amount of the compound may cause the adhesive to thicken or become thixotropic, resulting in a decrease in applicability. For this reason, it is preferable that the plate-like inorganic compound is nonionic, having no electric charge between layers.

[0047] The average particle size of the plate-like inorganic compound is not particularly limited, but is preferably 0.1 μm or more, and more preferably 1 μm or more, for example. If it is smaller than 0.1 μm, the detour path of oxygen molecules is not long, and the improvement of aroma retention cannot be expected sufficiently. The upper limit of the average particle size is not particularly limited, but if the particle size is too large, defects such as streaks may occur on the coated surface depending on the coating method. Therefore, as an example, the average particle size is preferably 100 μm or less, and more preferably 20 μm or less. In this specification, the average particle size of the plate-like inorganic compound refers to the particle size that appears most frequently when the particle size distribution of the plate-like inorganic compound is measured by a light scattering measuring device.

[0048] The aspect ratio of the plate-like inorganic compound is preferably high in order to improve aroma retention by the labyrinth effect of oxygen. Specifically, the aspect ratio is preferably 3 or more, more preferably 10 or more, and most preferably 40 or more.

[0049] The amount of the plate-like inorganic compound is arbitrary. As an example, the amount of the plate-like inorganic compound is 5 to 50 parts by mass when the total mass of the solid contents of the polyol composition (X1), the polyisocyanate composition (Y1), and the plate-like inorganic compound is 100 parts by mass.

[0050] The adhesive may contain a coupling agent (C2). Examples of the coupling agent (C2) include a silane coupling agent, a titanate-based coupling agent, an aluminum-based coupling agent, and the like.

[0051] Examples of the silane coupling agent include aminosilanes such as γ-aminopropyltriethoxysilane, γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β(aminoethyl)-γ-aminopropyltrimethyldimethoxysilane, and N-phenyl-γ-aminopropyltrimethoxysilane; epoxysilanes such as β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-glycidoxypropyltrimethoxysilane, and γ-glycidoxypropyltriethoxysilane; vinylsilanes such as vinyltris(β-methoxyethoxy)silane, vinyltriethoxysilane, vinyltrimethoxysilane, and γ-methacryloxypropyltrimethoxysilane; hexamethyldisilazane, γ-mercaptopropyltrimethoxysilane, and the like.

[0052] Examples of titanate coupling agents include tetraisopropoxytitanium, tetra-n-butoxytitanium, butyl titanate dimer, tetrastearyl titanate, titanium acetylacetonate, titanium lactate, tetraoctylene glycol titanate, titanium lactate, and tetrastearoxytitanium.

[0053] An example of the aluminum-based coupling agent is acetoalkoxyaluminum diisopropylate.

[0054] When the adhesive layer needs to be acid-resistant, it may contain a known acid anhydride (C3). Examples of the acid anhydride (C3) include phthalic anhydride, succinic anhydride, HET acid anhydride, hymic acid anhydride, maleic anhydride, tetrahydrophthalic anhydride, hexahydraphthalic anhydride, tetrabromophthalic anhydride, tetrachlorophthalic anhydride, trimellitic anhydride, pyromellitic anhydride, benzophenotetracarboxylic anhydride, 2,3,6,7-naphthalenetetracarboxylic dianhydride, 5-(2,5-oxotetrahydrofuryl)-3-methyl-3-cyclohexene-1,2-dicarboxylic anhydride, and styrene-maleic anhydride copolymer.

[0055] If necessary, a compound (C4) having an oxygen scavenging function may be further added. Examples of the compound (C4) having an oxygen scavenging function include low molecular weight organic compounds that react with oxygen, such as hindered phenols, vitamin C, vitamin E, organic phosphorus compounds, gallic acid, and pyrogallol, and transition metal compounds, such as cobalt, manganese, nickel, iron, and copper.

[0056] The curing reaction can be accelerated by using a catalyst (C5) as necessary. The catalyst (C5) is not particularly limited as long as it accelerates the urethane reaction of the polyol composition (X) and the polyisocyanate composition (Y), and examples thereof include metal catalysts, amine catalysts, aliphatic cyclic amide compounds, and titanium chelate complexes.

[0057] Examples of the metal catalyst include metal complex, inorganic metal, and organic metal catalysts. Examples of the metal complex catalyst include acetylacetonate salts of metals selected from the group consisting of Fe (iron), Mn (manganese), Cu (copper), Zr (zirconium), Th (thorium), Ti (titanium), Al (aluminum), and Co (cobalt), such as iron acetylacetonate, manganese acetylacetonate, copper acetylacetonate, and zirconia acetylacetonate. From the viewpoints of toxicity and catalytic activity, iron acetylacetonate (Fe(acac)3) or manganese acetylacetonate (Mn(acac)2) is preferred.

[0058] Examples of inorganic metal catalysts include those selected from Sn, Fe, Mn, Cu, Zr, Th, Ti, Al, Co, etc.

[0059] Examples of the organometallic catalyst include organozinc compounds such as zinc octylate, zinc neodecanoate, and zinc naphthenate; organotin compounds such as stannous diacetate, stannous dioctoate, stannous dioleate, stannous dilaurate, dibutyltin diacetate, dibutyltin dilaurate, dioctyltin dilaurate, dibutyltin oxide, and dibutyltin dichloride; organonickel compounds such as nickel octylate and nickel naphthenate; organocobalt compounds such as cobalt octylate and cobalt naphthenate; organobismuth compounds such as bismuth octylate, bismuth neodecanoate, and bismuth naphthenate; and titanium compounds such as tetraisopropyloxytitanate, dibutyltitanium dichloride, tetrabutyltitanate, and butoxytitanium trichloride.

[0060] Examples of the amine catalyst include triethylenediamine, 2-methyltriethylenediamine, quinuclidine, 2-methylquinuclidine, N,N,N',N'-tetramethylethylenediamine, N,N,N',N'-tetramethylpropylenediamine, N,N,N',N",N"-pentamethyldiethylenetriamine, N,N,N',N",N"-pentamethyl-(3-aminopropyl)ethylenediamine, N,N,N',N",N"-pentamethyldipropylenetriamine, N,N,N',N'-tetramethylhexamethylenediamine, bis(2-dimethylaminoethyl)ether, dimethylethanolamine, dimethylisopropanolamine, dimethylaminoethoxyethanol, N,N-dimethyl-N'-(2-hydroxyethyl)ethylenediamine, N,N-dimethyl-N'-(2-hydroxyethyl)propanediamine, bis(dimethylaminopropyl)amine, bis(dimethylaminopropyl)isopropanediamine, and the like. lopanolamine, 3-quinuclidinol, N,N,N',N'-tetramethylguanidine, 1,3,5-tris(N,N-dimethylaminopropyl)hexahydro-S-triazine, 1,8-diazabicyclo[5.4.0]undecene-7, N-methyl-N'-(2-dimethylaminoethyl)piperazine, N,N'-dimethylpiperazine, dimethylcyclohexylamine, N-methylmorpholine, N-ethylmorpholine, 1-methylimidazole, 1 ,2-dimethylimidazole, 1-isobutyl-2-methylimidazole, 1-dimethylaminopropylimidazole, N,N-dimethylhexanolamine, N-methyl-N'-(2-hydroxyethyl)piperazine, 1-(2-hydroxyethyl)imidazole, 1-(2-hydroxypropyl)imidazole, 1-(2-hydroxyethyl)-2-methylimidazole, 1-(2-hydroxypropyl)-2-methylimidazole, and the like.

[0061] Examples of the aliphatic cyclic amide compound include δ-valerolactam, ε-caprolactam, ω-enantholactam, η-capryllactam, β-propiolactam, etc. Among these, ε-caprolactam is more effective in promoting curing.

[0062] The titanium chelate complex is a compound whose catalytic activity is enhanced by ultraviolet irradiation, and a titanium chelate complex having an aliphatic or aromatic diketone as a ligand is preferred from the viewpoint of excellent curing acceleration effect. In the present invention, a titanium chelate complex having an alcohol having 2 to 10 carbon atoms as a ligand in addition to an aromatic or aliphatic diketone is preferred from the viewpoint of more remarkable effect of the present invention.

[0063] The catalyst (C5) may be used alone or in combination of two or more kinds. The amount of the catalyst (C5) is preferably 0.001 to 3 parts by mass, more preferably 0.01 to 2 parts by mass, per 100 parts by mass of the total solid content of the polyol composition (X) and the polyisocyanate composition (Y).

[0064] The adhesive may contain phosphoric acid (C6). Specific examples of phosphoric acid (C6) include phosphoric acid, pyrophosphoric acid, triphosphoric acid, methyl acid phosphate, ethyl acid phosphate, butyl acid phosphate, dibutyl phosphate, 2-ethylhexyl acid phosphate, bis(2-ethylhexyl)phosphate, isododecyl acid phosphate, butoxyethyl acid phosphate, oleyl acid phosphate, tetracosyl acid phosphate, 2-hydroxyethyl methacrylate acid phosphate, polyoxyethylene alkyl ether phosphate, etc. The amount of phosphoric acid (C6) to be blended is preferably 0.005 to 10% by mass, more preferably 0.01 to 1% by mass, of the total solid content of the adhesive.

[0065] In addition, the adhesive may contain a stabilizer (antioxidant, heat stabilizer, ultraviolet absorber, etc.), a plasticizer, an antistatic agent, a lubricant, an antiblocking agent, a colorant, a crystal nucleating agent, etc. These various additives may be added in advance to either one or both of the polyol composition (X1) and the polyisocyanate composition (Y1), or may be added when the polyol composition (X1) and the polyisocyanate composition (Y1) are mixed.

[0066] The adhesive used in the present invention may be in the form of either a solvent-based or solventless type. In this specification, the solvent-based adhesive refers to a form used in a method in which the adhesive is applied to a substrate, heated in an oven or the like to volatilize the organic solvent in the coating film, and then laminated to another substrate, that is, a so-called dry lamination method. Examples of the solvent used include toluene, xylene, methylene chloride, tetrahydrofuran, methyl acetate, ethyl acetate, n-propyl acetate, n-butyl acetate, acetone, methyl ethyl ketone (MEK), cyclohexanone, toluene, xylol, n-hexane, cyclohexane, and the like. Either or both of the polyol composition (X1) and the polyisocyanate composition (Y1) contain the above-mentioned organic solvent. In the case of a solvent-based adhesive, the solvent used as a reaction medium during the production of the constituent components of the polyol composition (X1) or the polyisocyanate composition (Y1) may also be used as a diluent during coating.

[0067] A solvent-free adhesive refers to a form used in a method in which an adhesive is applied to a substrate and then laminated to another substrate without a process of heating in an oven or the like to volatilize the solvent, that is, a so-called non-solvent lamination method. Neither the polyol composition (X1) nor the polyisocyanate composition (Y1) contains substantially the above-mentioned organic solvent. When the organic solvent used as a reaction medium in the manufacture of the components of the polyol composition (X1) or the polyisocyanate composition (Y1) or the raw material thereof cannot be completely removed and a trace amount of organic solvent remains in the polyol composition (X1) or the polyisocyanate composition (Y1), it is understood that the polyol composition (X1) contains substantially no organic solvent. In addition, when the polyol composition (X1) contains a low molecular weight alcohol, the low molecular weight alcohol reacts with the polyisocyanate composition (Y1) to become part of the coating film, so there is no need to volatilize it after coating. Therefore, such a form is also treated as a solvent-free adhesive.

[0068] When using an olefin-based substrate, if the adhesive is a solvent-based adhesive, the organic solvent tends to remain in the adhesive layer. If it is desired to suppress the amount of organic solvent remaining in the adhesive layer, a solventless adhesive can be selected.

[0069] Alternatively, when the adhesive used in the present invention is a solvent-based adhesive, it is preferable that the adhesive contains a drying aid (C7). This can suppress the organic solvent from remaining in the adhesive layer. Examples of the drying aid (C7) include isosorbide, isomannide, isoidide, triacetin, etc., and isosorbide is preferably used. The amount of the drying aid (C7) can be appropriately adjusted, but is, for example, 0.5% by mass or more and 50% by mass or less of the adhesive.

[0070] When the adhesive used in the present invention is a solventless type, it is preferable that the adhesive contains a reactive diluent (C8). This allows the adhesive to have a viscosity suitable for the non-solvent lamination method. Examples of the reactive diluent (C8) include isosorbide, isoidide, isomannide, furan diethanol, trans-tetrahydrofuran-3,4-diol, sorbitol, erythritol, etc., and isosorbide is preferably used. The amount of the reactive diluent (C8) can be appropriately adjusted, and as an example, it is 5% by mass or more and 90% by mass or less of the total amount of the polyester polyol (A) and the reactive diluent (C8), preferably 80% by mass or less, and more preferably 70% by mass or less.

[0071] When the adhesive is a solvent-based adhesive, the adhesive is applied to one substrate using a roll such as a gravure roll, and the organic solvent is evaporated by heating in an oven or the like, and then the other substrate is laminated to obtain the laminate of the present invention. It is preferable to perform an aging treatment after lamination. The aging temperature is preferably room temperature to 80°C, and the aging time is preferably 12 to 240 hours.

[0072] When the adhesive is a solventless type, the adhesive, which has been preheated to about 40°C to 100°C, is applied to one of the substrates using a roll such as a gravure roll, and the other substrate is immediately laminated to obtain the laminate of the present invention. It is preferable to carry out an aging treatment after lamination. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.

[0073] The amount of adhesive to be applied is adjusted as appropriate. For example, in the case of a solvent-based adhesive, the solid content is 1 g / m 2 More than 10g / m 2 Less than 1 g / m 2 More than 5g / m 2 Adjust the amount of adhesive applied as follows: For solvent-free adhesive, the amount of adhesive applied is, for example, 1 g / m 2 More than 10g / m 2 Less than 1 g / m 2 More than 5g / m 2 The following is the result.

[0074] (Coat layer) The coating agent used to form the coating layer is a two-component curing type coating agent containing a polyol composition (X2) containing a polyester polyol (D) and a polyisocyanate composition (Y2) containing an isocyanate compound (E). The coating layer is provided between the stretched polyethylene film and the ethylene-based heat seal layer.

[0075] As the polyester polyol (D), those having the same skeleton as the polyester polyols (A1) to (A3) (referred to as polyester polyols (D1), (D2) and (D3), respectively) can be used.

[0076] The hydroxyl value of the polyester polyol (D) is preferably 1 mgKOH / g or more and 350 mgKOH / g or less. When the polyester polyol (D) has an acid group, the acid value is preferably 200 mgKOH / g or less. There is no particular restriction on the lower limit, but as an example, it is 0.5 mgKOH / g or more. It may be 0 mgKOH / g.

[0077] The number average molecular weight of the polyester polyol (D) is particularly preferably 400 to 5000, since a crosslinking density excellent in balance between adhesion to the substrate and aroma retention can be obtained. The number average molecular weight is more preferably 500 to 2500. The number average molecular weight is calculated from the obtained hydroxyl value and the number of functional groups of the designed hydroxyl group.

[0078] The glass transition temperature of the polyester polyol (D) is preferably from 10°C to 80°C, more preferably from 20°C to 60°C, and even more preferably from 35°C to 60°C, in view of the balance between adhesion to the substrate and aroma retention.

[0079] The isocyanate compound (E) may be the same as the isocyanate compound (B). It is preferable to use an isocyanate having an aromatic ring or a derivative thereof (isocyanurate, allophanate, biuret, adduct, polyurethane polyisocyanate) (E1). Specific examples of the isocyanate compound (E1) include isocyanate compounds having a skeleton derived from xylylene diisocyanate, hydrogenated xylylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate.

[0080] In view of the good aroma retention properties, the isocyanate compound (E) is also preferably a polyurethane polyisocyanate (E2) obtained by reacting at least one selected from the polyester polyols (D1), (D2), and (D3) with an isocyanate having an aromatic ring or a derivative thereof (E1) in such a ratio that the equivalent ratio of the isocyanate group to the hydroxyl group, [NCO] / [OH], is 1.5 to 5.0.

[0081] The coating agent used in the present invention may be a solvent-based or solventless type, but is preferably a solvent-based coating agent containing an organic solvent (F) capable of diluting (dissolving) the polyester polyol (D). Examples of the organic solvent (F) include esters such as ethyl acetate, butyl acetate, and cellosolve acetate, ketones such as acetone, methyl ethyl ketone, isobutyl ketone, and cyclohexanone, ethers such as tetrahydrofuran and dioxane, aromatic hydrocarbons such as toluene and xylene, halogenated hydrocarbons such as methylene chloride and ethylene chloride, dimethyl sulfoxide, and dimethyl sulfamide. The organic solvent used as a reaction medium during the production of the components of the polyol composition (X2) or polyisocyanate composition (Y2) may also be used as a diluent during coating. It is preferable to use at least one of esters and ketones.

[0082] When the coating agent used in the present invention is a solvent-based coating agent, it may contain a drying aid (G). The drying aid (G) has a function of promoting the volatilization of the organic solvent (F). Examples of the drying aid (F) include isosorbide, isomannide, isoidide, triacetin, and trimethylolpropane. It is preferable to use at least one selected from isosorbide and trimethylolpropane. In general, the organic solvent tends to be difficult to volatilize from a composition containing a polyester polyol and an organic solvent, but the coating agent using the above-mentioned polyester polyols (D1) to (D3) in particular can form a coating film with excellent gas barrier properties, but on the other hand, due to its excellent gas barrier properties, it tends to easily hinder the volatilization of the organic solvent. By containing the drying aid (G), the organic solvent (F) becomes easier to volatilize in the drying process, the gas barrier coating agent has excellent drying properties, and the organic solvent (F) is less likely to remain in the cured coating film.

[0083] In addition, it is preferable that the drying aid (G) has a hydroxyl group. This allows it to react with the isocyanate compound (E) and be incorporated into the cured coating film, so unlike additives that do not have functional groups, there is no risk of it migrating from the coating layer to other layers over time, and it has little effect on the physical properties of the coating layer over time. The drying process here refers to a process in which the polyol composition (X2) and the polyisocyanate composition (Y2) are mixed, applied to a substrate, and then passed through an oven to volatilize the organic solvent (F) contained in the coating film of the coating agent.

[0084] From the viewpoint of effectively suppressing the residue of the organic solvent (F), the blending amount of the drying aid (G) is preferably 0.5% by mass or more, more preferably 1% by mass or more, of the total solid content of the coating agent, and from the viewpoint of the blocking resistance of the coating agent, it is preferably 30% by mass or less, more preferably 10% by mass or less.

[0085] The coating agent used in the present invention may contain components other than the above-mentioned components. These components may be contained in either or both of the polyol composition (X2) and the polyisocyanate composition (Y2), or may be prepared separately and mixed just before application of the coating agent. Examples of other components (H) include inorganic fillers (H1), antiskinning agents (H2), coupling agents (H3), catalysts (H4), and phosphoric acids (H5).

[0086] As the inorganic filler (H1), the same fillers as those exemplified as the inorganic filler (C1) can be used. From the viewpoint of the balance between the gas barrier property and the drying property of the organic solvent (F), the proportion of the inorganic filler (H1) in the total solid content of the polyol composition (X2) and the polyisocyanate composition (Y2) is preferably 0.001 to 50 mass%, more preferably 0.01 to 40 mass%.

[0087] As the anti-skinning agent (H2), an organic solvent having a higher boiling point than the organic solvent (F) and having a high solubility in the polyester polyol (D) is used. By including the anti-skinning agent (H2), it is possible to prevent the surface of the coating layer from drying before the organic solvent (F) volatilizes from inside the coating film of the coating agent, thereby preventing the volatilization of the organic solvent (F) from being hindered.

[0088] Specific examples of the antiskinning agent (H2) include propylene glycol monomethyl ether, ethyl cellosolve, propyl acetate, and butyl acetate.

[0089] From the viewpoint of the balance between the gas barrier property and the drying property of the organic solvent (F), the blending amount of the anti-skinning agent (H2) is preferably 0.1 to 10 parts by mass, and more preferably 1 to 5 parts by mass, per 100 parts by mass of the total amount (including volatile components such as the organic solvent (F)) of the polyol composition (X2) and the polyisocyanate composition (Y2) excluding the anti-skinning agent (H2).

[0090] As the coupling agent (H3), the same ones as those exemplified as the coupling agent (C2) can be used.

[0091] The catalyst (H4) may be the same as those exemplified as the catalyst (C5), and may be used alone or in combination of two or more. The amount of the catalyst (H4) is preferably 0.001 to 3 parts by mass, more preferably 0.01 to 2 parts by mass, per 100 parts by mass of the total solid content of the polyol composition (X2) and the polyisocyanate composition (Y2).

[0092] As the phosphoric acid (H5), the same as those exemplified as the phosphoric acid (C6) can be used. When the coating agent used in the present invention contains the phosphoric acid (H5), the content is preferably 1 ppm or more and 200 ppm or less of the total solid content of the coating agent.

[0093] In addition to the above-mentioned components, the coating agent used in the present invention may contain leveling agents, polymethyl methacrylate-based organic fine particles, defoamers, sagging prevention agents, wetting and dispersing agents, viscosity regulators, ultraviolet absorbers, metal deactivators, peroxide decomposers, flame retardants, reinforcing agents, plasticizers, lubricants, surface conditioners, rust inhibitors, fluorescent brightening agents, inorganic heat ray absorbers, flame retardants, antistatic agents, dehydrating agents, known and commonly used thermoplastic elastomers, tackifiers, melamine resins, reactive elastomers, etc. The amounts of these additives to be added are appropriately adjusted within a range that does not impair the desired properties of the coating agent of the present invention.

[0094] The polyol composition (X2) and the polyisocyanate composition (Y2) are preferably used after adjusting the molar ratio ([NCO] / [OH]) of the isocyanate groups contained in the polyisocyanate composition (Y2) to the hydroxyl groups contained in the polyol composition (X2) to be 0.3 to 6.

[0095] The coating amount (solid content) of the coating layer can be appropriately adjusted. For example, it is 1.0 g / m 2 More than 4.0g / m 2 The following is the result.

[0096] (Printing layer) The laminate of the present invention may be provided with a printed layer. The printed layer is a layer on which characters, figures, symbols, other desired patterns, etc. are printed using liquid ink. In this specification, liquid ink is a general term for solvent-based inks used in gravure printing or flexographic printing. The liquid ink may contain resin, colorant, and solvent as essential components, or may be a so-called clear ink that contains resin and solvent and does not substantially contain colorant. The printed layer is provided, for example, on either one side of the stretched polyethylene film directly or via a layer such as a primer layer that has receptivity to liquid ink. The printed layer may be provided on the entire surface of the stretched polyolefin film, or may be provided only on a part of the film.

[0097] The resin used in the liquid ink is not particularly limited, and examples thereof include acrylic resin, polyester resin, styrene resin, styrene-maleic acid resin, maleic acid resin, polyamide resin, polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, vinyl chloride-acrylic copolymer resin, ethylene-vinyl acetate copolymer resin, vinyl acetate resin, polyvinyl chloride resin, chlorinated polypropylene resin, cellulose-based resin, epoxy resin, alkyd resin, rosin-based resin, rosin-modified maleic acid resin, ketone resin, cyclized rubber, chlorinated rubber, butyral, petroleum resin, etc., and one or more of them can be used in combination. Preferably, at least one or two or more selected from polyurethane resin, vinyl chloride-vinyl acetate copolymer resin, and cellulose-based resin are used.

[0098] Colorants used in liquid inks include inorganic pigments such as titanium oxide, red iron oxide, antimony red, cadmium red, cadmium yellow, cobalt blue, Prussian blue, ultramarine, carbon black, and graphite; organic pigments such as soluble azo pigments, insoluble azo pigments, azo lake pigments, condensed azo pigments, copper phthalocyanine pigments, and condensed polycyclic pigments; and extender pigments such as calcium carbonate, kaolin clay, barium sulfate, aluminum hydroxide, and talc.

[0099] The organic solvent used in the liquid ink preferably does not contain an aromatic hydrocarbon-based organic solvent. More specifically, examples of the organic solvent include alcohol-based organic solvents such as methanol, ethanol, n-propanol, isopropanol, and butanol, ketone-based organic solvents such as acetone, methyl ethyl ketone, and methyl isobutyl ketone, ester-based organic solvents such as methyl acetate, ethyl acetate, propyl acetate, and butyl acetate, aliphatic hydrocarbon-based organic solvents such as n-hexane, n-heptane, and n-octane, and alicyclic hydrocarbon-based organic solvents such as cyclohexane, methylcyclohexane, ethylcyclohexane, cycloheptane, and cyclooctane, and these may be used alone or in combination of two or more.

[0100] (Heat-resistant coating layer) The laminate of the present invention is also preferably provided with a heat-resistant coating layer. The heat-resistant coating layer is provided on the stretched polyethylene film directly or via a printed layer. When the laminate of the present invention is made into a bag, the heat-resistant coating layer is located as the outermost layer from the content, i.e., on the opposite side of the stretched polyethylene film to the side on which the coating layer is applied, and is the layer that comes into contact with the heat seal bar during bag making. It is also preferable that the stretched polyethylene film is provided with heat-resistant coating layers on both sides.

[0101] The heat-resistant coating layer is provided by applying a heat-resistant coating agent to the stretched polyethylene film. Examples of the heat-resistant coating agent include those containing a compound having a cellulose skeleton, a benzene ring skeleton, an isocyanuric ring skeleton, or an alicyclic skeleton, whose homopolymer has a glass transition temperature (hereinafter sometimes referred to as Tg) of 100° C. or higher. Specific examples include cellulose derivatives such as cellulose nitrate, cellulose acetate, cellulose acetate propionate, and cellulose acetate butyrate; polyester resins having a benzene ring derived from phthalic acid, naphthalene dicarboxylic acid, and ethylene oxide (hereinafter sometimes referred to as EO) adducts of bisphenol A, and / or an alicyclic skeleton derived from cyclopentanediol, dimethyloltricyclodecane, and the like; aromatic isocyanates such as diphenylmethane diisocyanate, toluene diisocyanate, xylene diisocyanate, and naphthalene diisocyanate; alicyclic isocyanates such as isocyanuric triisocyanate and norbornene diisocyanate; and / or urethane resins made from isocyanuric triisocyanate and polyols and / or tris(2-hydroxyethyl)isocyanurate; styrene, fluoro, and the like. Examples of the coating agent include a coating agent containing a compound having a benzene ring and an unsaturated double bond, such as phenoxydiethylene glycol acrylate, and / or a compound having an alicyclic structure and an unsaturated double bond, such as isobornyl acrylate and dicyclopentanyl acrylate, and a radical copolymer such as (meth)acrylate; and a two-component curing coating agent that uses at least one selected from aromatic isocyanates such as diphenylmethane diisocyanate, toluene diisocyanate, xylylene diisocyanate and naphthalene diisocyanate, alicyclic isocyanates such as isophorone diisocyanate and norbornene diisocyanate, derivatives of these isocyanates, and isocyanuric triisocyanate as a curing agent, and is a composition containing a resin having a functional group reactive with an isocyanate group, such as a hydroxyl group, an amino group, or a carboxyl group, as a base.

[0102] The heat-resistant coating agent may further contain a resin having a low Tg in consideration of adhesion to the stretched polyethylene film. The total amount of the cellulose skeleton, benzene ring skeleton, isocyanuric ring skeleton and alicyclic skeleton is preferably 20 to 90 mass %, more preferably 30 to 80 mass %, of the solid content of the heat-resistant coating agent.

[0103] The heat-resistant coating agent preferably contains inorganic particles such as alumina, magnesia, titania, zirconia, and silica (quartz, fumed silica, precipitated silica, silicic anhydride, fused silica, crystalline silica, and ultrafine amorphous silica) as aggregates. This allows the formation of a coating layer with better heat resistance. Alternatively, the heat-resistant coating agent preferably contains particles such as boron nitride, aluminum nitride, alumina oxide, titanium oxide, magnesium oxide, zinc oxide, and silicon oxide, which are compounds with excellent thermal conductivity. The inorganic particles may be used alone or in combination. The shape of the silica particles is not particularly limited, and spherical, hollow, porous, rod-like, plate-like, fibrous, or amorphous silica particles can be used. For example, commercially available hollow silica particles such as Silinax manufactured by Nittetsu Mining Co., Ltd. can be used.

[0104] The primary particle diameter of the inorganic particles is preferably in the range of 5 to 200 nm. If it is 5 nm or more, the inorganic fine particles in the dispersion are well dispersed, and if it is within 200 nm, the strength of the cured product is good. It is more preferably 10 nm to 100 nm. The blending amount of the inorganic particles can be adjusted as appropriate, but as an example, it is 5 to 90% by weight, and preferably 20% by mass or more, of the total solid content of the heat-resistant coating agent containing the inorganic particles.

[0105] The heat-resistant coating agent may contain wax, silicon additives, organic beads, etc., for the purpose of preventing damage to the coating film, preventing blocking during laminate formation, imparting processability during bag making after the laminate is created, etc. Specific examples include waxes such as amide wax, polypropylene wax, polyethylene wax, paraffin wax, carnauba wax, rice wax, ethylene oxide (EO) adducts of dimethylsiloxane, silicon additives of silicon modifications, and organic beads made of acrylic, nylon, urethane, or epoxy.

[0106] The heat-resistant coating agent is a solution or dispersion of these components in a solvent, such as water, toluene, xylene, Solvesso #100, Solvesso #150, and other aromatic hydrocarbon organic solvents, hexane, methylcyclohexane, heptane, octane, decane, and other aliphatic hydrocarbon organic solvents, and methyl acetate, ethyl acetate, isopropyl acetate, normal propyl acetate, butyl acetate, amyl acetate, ethyl formate, butyl propionate, and other ester-based organic solvents. Examples of water-miscible organic solvents include alcohols such as methanol, ethanol, propanol, butanol, and isopropyl alcohol, ketones such as acetone, methyl ethyl ketone, and cyclohexanone, and glycol ethers such as ethylene glycol (mono, di) methyl ether, ethylene glycol (mono, di) ethyl ether, ethylene glycol monopropyl ether, ethylene glycol monoisopropyl ether, monobutyl ether, diethylene glycol (mono, di) methyl ether, diethylene glycol (mono, di) ethyl ether, diethylene glycol monoisopropyl ether, diethylene glycol monobutyl ether, triethylene glycol (mono, di) methyl ether, propylene glycol (mono, di) methyl ether, propylene glycol monopropyl ether, propylene glycol monobutyl ether, and dipropylene glycol (mono, di) methyl ether. These can be used alone or in combination of two or more. In order to perform coating more effectively, a defoamer or a leveling agent may be used.

[0107] (Other layers) The laminate of the present invention may include layers other than those described above. For example, as a layer having gas barrier properties, an inorganic vapor deposition layer or a coating layer having gas barrier properties may be included. The inorganic vapor deposition layer is a layer having gas barrier properties that prevents the permeation of oxygen gas and water vapor gas, and is a vapor deposition layer made of an inorganic substance or an inorganic oxide. Examples of inorganic substances or inorganic oxides include aluminum, alumina, silica, etc., which may be used alone or in combination of two or more types such as binary vapor deposition of silica and alumina. Two or more inorganic vapor deposition layers may be provided. When two or more inorganic vapor deposition layers are provided, each may have the same composition or different compositions.

[0108] The inorganic vapor deposition layer can be provided on the resin layer by a conventionally known method. Examples of the method for forming the inorganic vapor deposition layer include physical vapor deposition methods (PVD methods) such as vacuum deposition, sputtering, and ion plating, and chemical vapor deposition methods (CVD methods) such as plasma chemical vapor deposition, thermal chemical vapor deposition, and photochemical vapor deposition.

[0109] The inorganic vapor deposition layer has a thickness of, for example, 1 to 200 nm. When the inorganic vapor deposition layer is an aluminum vapor deposition layer, the thickness is, for example, 1 to 100 nm, and when the inorganic vapor deposition layer is a silica or alumina vapor deposition layer, the thickness is, for example, 1 to 100 nm.

[0110] The coating layer having gas barrier properties is provided by applying and drying a coating agent containing, for example, a polyvinyl gas barrier resin. Such coating agents can be conventionally known, and examples include those containing a vinyl alcohol polymer such as polyvinyl alcohol, ethylene vinyl alcohol, and polyvinyl butyral, and an aqueous solvent. The vinyl alcohol polymer may have a reactive functional group other than a hydroxyl group, such as an acetoacetyl group, a carboxyl group, an anionic carboxyl group, a sulfonic acid group, or an anionic sulfonic acid group. These may be used alone or in combination of two or more.

[0111] Examples of the aqueous solvent include water, glycols such as ethylene glycol, diethylene glycol, triethylene glycol, tetraethylene glycol, propylene glycol, polyethylene glycol, and polypropylene glycol; diols such as butanediol, pentanediol, and hexanediol; glycol esters such as propylene glycol laurate; diethylene glycol ethers such as diethylene glycol monoethyl, diethylene glycol monobutyl, diethylene glycol monohexyl, and carbitol; glycol ethers such as propylene glycol ether, dipropylene glycol ether, and cellosolve containing triethylene glycol ether; alcohols such as methanol, ethanol, isopropyl alcohol, 1-propanol, 2-propanol, 1-butanol, 2-butanol, butyl alcohol, and pentyl alcohol; lactones such as sulfolane, esters, ketones, and γ-butyrolactone, lactams such as N-(2-hydroxyethyl)pyrrolidone, and polyalkylene oxide adducts of glycerin and the like. The aqueous solvents can be used alone or in combination of two or more kinds.

[0112] The coating agent may further contain a layered inorganic compound, a crosslinking agent capable of reacting with a functional group possessed by the vinyl alcohol polymer, an inorganic filler, an antifoaming agent, a stabilizer (antioxidant, heat stabilizer, ultraviolet absorber, etc.), a plasticizer, an antistatic agent, a lubricant, an antiblocking agent, a colorant, a leveling agent, etc.

[0113] As a coating agent for forming a coating layer having gas barrier properties, a commercially available product can be used, and examples thereof include EXEVIA (registered trademark) manufactured by Sumitomo Chemical Co., Ltd., the SunBar (registered trademark) series manufactured by Sun Chemical Co., Ltd., and TAKELAC WPB (registered trademark) series manufactured by Mitsui Chemicals, Inc.

[0114] However, laminates including an inorganic vapor deposition layer or a coating layer having gas barrier properties often have sufficient aroma retention due to their effects, and therefore the present invention is preferably applied to laminates that do not include an inorganic vapor deposition layer or a coating layer having gas barrier properties.

[0115] Similarly, laminates containing a film made of, for example, polyester resin often have sufficient aroma retention by themselves, and therefore the present invention is preferably applied to laminates that do not contain such substrates.

[0116] It is also preferable that the sheet further comprises a stretched polyethylene film. In this case, the stretched polyethylene film used may be the same as that described above.

[0117] Suitable examples of the laminate of the present invention include, for example, (1) Stretched polyethylene film / coating layer / printing layer / adhesive layer / ethylene-based heat seal layer (2) Stretched polyethylene film / printed layer / coating layer / adhesive layer / ethylene-based heat seal layer (3) Stretched polyethylene film / coating layer / adhesive layer / ethylene-based heat seal layer (4) Heat-resistant coating layer / stretched polyethylene film / coating layer / printing layer / adhesive layer / ethylene-based heat seal layer (5) Heat-resistant coating layer / stretched polyethylene film / printing layer / coating layer / adhesive layer / ethylene-based heat seal layer (6) Heat-resistant coating layer / stretched polyethylene film / coating layer / adhesive layer / ethylene-based heat seal layer

[0118] (7) Stretched polyethylene film / coating layer / printing layer / adhesive layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer (8) Stretched polyethylene film / printing layer / coating layer / adhesive layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer (9) Stretched polyethylene film / printing layer / adhesive layer / stretched polyethylene film / coating layer / adhesive layer / ethylene-based heat seal layer (10) Stretched polyethylene film / printing layer / adhesive layer / coating layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer, (11) Stretched polyethylene film / coating layer / adhesive layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer (12) Stretched polyethylene film / adhesive layer / coating layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer (13) Stretched polyethylene film / adhesive layer / stretched polyethylene film / coat layer / adhesive layer / ethylene-based heat seal layer

[0119] (14) Heat-resistant coating layer / stretched polyethylene film / coating layer / printing layer / adhesive layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer (15) Heat-resistant coating layer / stretched polyethylene film / printing layer / coating layer / adhesive layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer (16) Heat-resistant coating layer / stretched polyethylene film / printing layer / adhesive layer / stretched polyethylene film / coating layer / adhesive layer / ethylene-based heat seal layer (17) heat-resistant coating layer / stretched polyethylene film / printing layer / adhesive layer / coating layer / stretched polyethylene film / adhesive layer / ethylene-based heat seal layer, (18) Heat-resistant coating layer / oriented polyethylene film / coating layer / adhesive layer / oriented polyethylene film / adhesive layer / ethylene-based heat seal layer (19) Heat-resistant coating layer / oriented polyethylene film / adhesive layer / coating layer / oriented polyethylene film / adhesive layer / ethylene-based heat seal layer (20) Heat-resistant coating layer / stretched polyethylene film / adhesive layer / stretched polyethylene film / coating layer / adhesive layer / ethylene-based heat seal layer Examples of the stretched polyethylene film include, but are not limited to, MDOPE film or BOPE film.

[0120] When two adhesive layers are provided as in the above configuration examples (7) to (20), at least one of them may be the above adhesive layer, and it is preferable that both layers are the above adhesive layers. When two layers of stretched polyethylene film are included as in the above configuration examples (7) to (20), these may be different types of films or the same type of film. The thicknesses may be approximately the same (meaning that the difference in thickness is within 5 μm, although there may be differences within the range of manufacturing tolerance. Hereinafter, "approximately the same thickness of film or layer" means the same thing), or they may be different. It is preferable that the thicknesses of the two layers of stretched polyethylene film are the same, or that the thickness of the stretched polyethylene film located on the outer side as viewed from the contents when the bag is made is thicker. It is preferable that the difference in thickness of the two layers of stretched polyethylene film is 20 μm or less. When two layers of stretched polyethylene film are included as in the above configuration examples (7) to (20), it is preferable that the coating layer is provided on the stretched polyethylene film closer to the ethylene-based heat seal layer as in the configuration examples (9), (10), (12), (13), (16), (17), (19), and (20).

[0121] <Packaging material> The laminate of the present invention is used as a packaging material for liquid products such as liquid soap (hand soap), body soap, shampoo, rinse, conditioner, dishwashing detergent, liquid laundry detergent, fabric softener, sodium bicarbonate electrolytic water, liquid bath additives, body milk, and other liquid products. The form of such a packaging material is not particularly limited, but as an example, a so-called standing pouch can be formed by overlapping a front member and a back member, heat-sealing the left and right side edges of the overlapping members to form a side seal portion, folding a bottom member, and heat-sealing the outer peripheral edge of the overlapping members to form a bottom seal portion. At least one of the left and right side edges of the packaging material may be provided with a notch portion for facilitating opening of the packaging material, and may further be subjected to half-cut processing. In addition, a means for facilitating pouring of the contents may be provided at one corner of the upper part of the packaging material. Such means include a method of heat-sealing a front member and a back member together to provide a tapered spout that faces diagonally outward and upward, and a method of joining a spout formed by separately molding.

[0122] Among the members constituting the packaging material of the present invention, all members made of a laminate are manufactured from the laminate of the present invention. However, the members may all be laminates of the same configuration, or may be different. For example, in a first embodiment of the packaging material of the present invention, the front member and the back member are selected from the above-mentioned laminate configuration examples (1), (2), (4), and (5), and the bottom member is selected from the laminate configuration examples (3) and (6). In the first embodiment, the film thickness of the stretched polyethylene film in the front member and the back member is approximately the same. The film thickness of the stretched polyethylene film in the bottom member may be approximately the same as the film thickness of the stretched polyethylene film in the front member and the back member, or may be thinner or thicker. The difference between the film thickness of the stretched polyethylene film in the bottom member and the film thickness of the stretched polyethylene film in the front member and the back member is within 20 μm.

[0123] In the first embodiment, the thickness of the ethylene-based heat seal layer in the front member and the back member is approximately the same. The thickness of the ethylene-based heat seal layer in the bottom member may be approximately the same as the thickness of the heat seal layer in the front member and the back member, or may be thinner or thicker. The difference between the thickness of the ethylene-based heat seal layer in the bottom member and the thickness of the ethylene-based heat seal layer in the front member and the back member is within 30 μm.

[0124] In a second embodiment of the packaging material of the present invention, the front member, the back member, and the bottom member are all selected from the laminate configuration examples (1), (2), (4), and (5) described above, and may all be made of the same laminate configuration example or may be different. In the second embodiment, the thickness of the stretched polyethylene film in the front member and the back member is approximately the same. The thickness of the stretched polyethylene film in the bottom member may be approximately the same as the thickness of the stretched polyethylene film in the front member and the back member, or may be thinner or thicker. The difference between the thickness of the stretched polyethylene film in the bottom member and the thickness of the stretched polyethylene film in the front member and the back member is within 20 μm.

[0125] In the second embodiment, the thickness of the ethylene-based heat seal layer in the front member and the back member is approximately the same. The thickness of the ethylene-based heat seal layer in the bottom member may be approximately the same as the thickness of the heat seal layer in the front member and the back member, or may be thinner or thicker. The difference between the thickness of the ethylene-based heat seal layer in the bottom member and the thickness of the ethylene-based heat seal layer in the front member and the back member is within 30 μm.

[0126] In a third embodiment of the packaging material of the present invention, the front member, the back member, and the bottom member are all selected from the laminate configuration examples (3) and (6) described above. They may all be made of the same laminate configuration example, or they may be different. In the third embodiment, the film thickness of the stretched polyethylene film in the front member and the back member is approximately the same. The film thickness of the stretched polyethylene film in the bottom member may be approximately the same as the film thickness of the stretched polyethylene film in the front member and the back member, or it may be thinner or thicker. The difference between the film thickness of the stretched polyethylene film in the bottom member and the film thickness of the stretched polyethylene film in the front member and the back member is within 20 μm.

[0127] In the third embodiment, the thickness of the ethylene-based heat seal layer in the front member and the back member is approximately the same. The thickness of the ethylene-based heat seal layer in the bottom member may be approximately the same as the thickness of the heat seal layer in the front member and the back member, or may be thinner or thicker. The difference between the thickness of the ethylene-based heat seal layer in the bottom member and the thickness of the ethylene-based heat seal layer in the front member and the back member is within 30 μm.

[0128] In a fourth embodiment of the packaging material of the present invention, the front member and the back member are selected from the laminate configuration examples (7) to (20) described above, and the bottom member is selected from the laminate configuration examples (1) to (6). In the fourth embodiment, the front member and the back member are preferably made of a laminate of the same configuration example.

[0129] In the fourth embodiment, the thickness of the ethylene-based heat seal layer in the front member and the back member is approximately the same. The thickness of the ethylene-based heat seal layer in the bottom member may be approximately the same as the thickness of the heat seal layer in the front member and the back member, or may be thinner or thicker. The difference between the thickness of the ethylene-based heat seal layer in the bottom member and the thickness of the ethylene-based heat seal layer in the front member and the back member is within 50 μm.

[0130] In a fifth embodiment of the packaging material of the present invention, the front member, the back member, and the bottom member are all selected from the laminate configuration examples (7) to (20) described above. They may all be made of the same laminate configuration example, or they may all be different. In the fifth embodiment, it is preferable that the front member and the back member are made of the same laminate configuration example.

[0131] In the fifth embodiment, the thickness of the ethylene-based heat seal layer in the front member and the back member is approximately the same. The thickness of the ethylene-based heat seal layer in the bottom member may be approximately the same as the thickness of the heat seal layer in the front member and the back member, or may be thinner or thicker. The difference between the thickness of the ethylene-based heat seal layer in the bottom member and the thickness of the ethylene-based heat seal layer in the front member and the back member is within 50 μm. EXAMPLES

[0132] The present invention will be described below with reference to examples and comparative examples, but the present invention is not limited thereto. The blending compositions and other numerical values ​​are based on mass unless otherwise specified.

[0133] <Adjusting the adhesive> (Adhesive 1) (Polyol composition (X1-1)) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 79.10 parts of ethylene glycol, 74.06 parts of phthalic anhydride, 73.07 parts of adipic acid, and 0.01 parts of titanium tetraisopropoxide were charged, and the temperature at the top of the rectification tube was gradually heated so that it did not exceed 100 ° C., and the internal temperature was maintained at 220 ° C. When the acid value became 1 mg KOH / g or less, the esterification reaction was terminated, and 0.03 parts of phosphoric acid were added while further heating to 60 ° C. and stirred for 1 hour, to obtain a polyester polyol with a number average molecular weight of 800. The hydroxyl value was 143.2 mg KOH / g. The obtained polyester polyol was used as a polyol composition (X1-1).

[0134] (Polyisocyanate composition (Y1-1)) In a polyester reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 79.27 parts of ethylene glycol, 59.25 parts of phthalic anhydride, 87.68 parts of adipic acid, and 0.02 parts of titanium tetraisopropoxide were charged, and the internal temperature was maintained at 220° C. by gradually heating so that the temperature at the top of the distillation tube did not exceed 100° C. When the acid value became 1 mgKOH / g or less, the esterification reaction was terminated, and 0.06 parts of phosphoric acid was added while further heating to 60° C. and stirred for 1 hour, to obtain a polyester intermediate (y1-1) having a number average molecular weight of 850.

[0135] 69.06 parts of xylylene diisocyanate and 30.61 parts of Millionate MN (a mixture of 4,4'-diphenylmethane diisocyanate and 2,4'-diphenylmethane diisocyanate) were placed in a reaction vessel equipped with a stirrer, a nitrogen gas introduction tube, a Snyder tube, a cooling condenser, and a dropping funnel, and the mixture was stirred while being heated to 70 ° C., and 100.33 parts of polyester intermediate (y1-1) were dropped using a dropping funnel over 2 hours, and the mixture was further stirred for 4 hours to obtain a polyisocyanate composition (Y1-1). The NCO% measured according to JIS-K1603 was 15.4%.

[0136] An adhesive 1 was obtained by mixing 60 parts of a polyol composition (X1-1) and 100 parts of a polyisocyanate composition (Y1-1).

[0137] (Adhesive 2) (Polyol composition (X1-2)) In a polyester reaction vessel equipped with an agitator, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 20.98 parts of ethylene glycol, 0.12 parts of glycerin, 50.94 parts of 1,3,5-tris(2-hydroxyethyl)isocyanuric acid, and 50.41 parts of phthalic anhydride were charged, and the temperature at the top of the rectification tube was gradually heated so that it did not exceed 100 ° C., and the internal temperature was maintained at 220 ° C. When the acid value became 1 mg KOH / g or less, the esterification reaction was terminated, and a polyester polyol with a number average molecular weight of 670 was obtained. The hydroxyl value was 230.2 mg KOH / g. The obtained polyester polyol was used as a polyol composition (X1-2).

[0138] (Polyisocyanate composition (Y1-2)) In a polyester reaction vessel equipped with an agitator, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 51.06 parts of ethylene glycol and 63.30 parts of phthalic anhydride were charged, and the temperature was gradually increased so that the temperature at the top of the distillation tube did not exceed 100°C, and the internal temperature was maintained at 220°C. When the acid value became 1 mgKOH / g or less, the esterification reaction was terminated, and 0.01 parts of phosphoric acid were added to obtain a polyester intermediate (y1-2) with a number average molecular weight of 340. The hydroxyl value was 331.0 mgKOH / g.

[0139] 125.00 parts of xylylene diisocyanate was placed in a reaction vessel equipped with a stirrer, nitrogen gas inlet tube, Snyder tube, cooling condenser, and dropping funnel, and stirred while heating to 70°C. 82.00 parts of polyester intermediate (y1-2) was dropped using the dropping funnel over 2 hours, and further stirred for 4 hours to obtain isocyanate compound (Y1-2). NCO% measured according to JIS-K1603 was 16.6%.

[0140] 100 parts of the polyol composition (X1-2) and 32 parts by mass of the polyisocyanate composition (Y1-2) were mixed and diluted with ethyl acetate to a solid content of 53%, thereby obtaining adhesive 2.

[0141] (Adhesive 3) (Polyol composition (X1')) A reactor equipped with a stirrer, nitrogen gas inlet tube, Snyder tube, cooling condenser, and dropping funnel was charged with 73.98 parts of castor oil and 51.02 parts of polypropylene glycol (molecular weight about 4000), and the mixture was stirred while being heated to 70 ° C., and 2.55 parts of Millionate MN (a mixture of 4,4'-diphenylmethane diisocyanate and 2,4'-diphenylmethane diisocyanate) were dropped using the dropping funnel, and the mixture was further stirred for 4 hours to obtain a polyol composition (X1'). The hydroxyl value was 115.0 mg KOH / g.

[0142] (Polyisocyanate composition (Y1')) A reaction vessel equipped with a stirrer, a nitrogen gas inlet tube, a Snyder tube, a cooling condenser, and a dropping funnel was charged with 114.00 parts of Millionate MN (a mixture of 4,4'-diphenylmethane diisocyanate and 2,4'-diphenylmethane diisocyanate) and stirred while heating to 70 ° C., and 28.16 parts of polypropylene glycol (molecular weight about 400) and 58.44 parts of polypropylene glycol (molecular weight about 1000) were dropped using the dropping funnel over 2 hours, and further stirred for 4 hours to obtain a polyisocyanate composition (Y1'). The NCO% measured according to JIS-K1603 was 13.5%.

[0143] An adhesive 3 was obtained by mixing 50 parts of the polyol composition (X1') and 100 parts of the polyisocyanate composition (Y1').

[0144] <Preparation of coating agent> (Synthesis of polyester polyol (D)) In a polyester reaction vessel equipped with an agitator, a nitrogen gas inlet tube, a Snyder tube, and a condenser, 1.26 parts of ethylene glycol, 26.76 parts of glycerin, and 40.99 parts of phthalic anhydride were charged, and the temperature was gradually increased so that the temperature at the top of the distillation tube did not exceed 100°C, and the internal temperature was maintained at 190°C. When the acid value reached 40 mgKOH / g, 7.33 parts of phthalic anhydride were added, and when the acid value reached 70 mgKOH / g, the esterification reaction was terminated. A polyester polyol (D) with a number average molecular weight of 900 was obtained. The hydroxyl value was 165 mgKOH / g.

[0145] (Preparation of coating agent) A coating agent was prepared using 10 parts by mass of polyester polyol (D), 4.3 parts by mass of isosorbide, 16.0 parts of BARRISURF HX (manufactured by IMERYS, kaolin / non-swelling, interlayer nonionic, plate-like, average particle size / 1.5 μm, aspect ratio / approximately 100), 15.0 parts of XDI-TMP adduct, 23.0 parts of ethyl acetate, 23.0 parts of methyl ethyl ketone, and 1.0 part of propylene glycol monomethyl ether.

[0146] <Manufacture of Laminate> Example 1 A coating agent was applied to a BOPE film with a thickness of 40 μm, and the dry coating thickness was 2.0 g / m 2 The adhesive 1 was applied to the substrate using a bar coater so that the coating amount was 2.5 g / m. 2 (solid content), which was then laminated with an LLDPE film having a thickness of 60 μm, and aging was carried out at 40° C. for 3 days to obtain a laminate of Example 1.

[0147] Example 2 A coating agent was applied to a BOPE film with a thickness of 40 μm, and the dry coating thickness was 2.0 g / m 2 The adhesive 2 was applied to the substrate using a bar coater so that the coating amount was 3.5 g / m. 2 (solid content), which was then laminated with an LLDPE film having a thickness of 60 μm, and aging was carried out at 40° C. for 4 days to obtain a laminate of Example 1.

[0148] Comparative Example 1 A laminate of Comparative Example 1 was obtained in the same manner as in Example 1, except that Adhesive 3 was used instead of Adhesive 1. Comparative Example 2 A laminate of Comparative Example 2 was obtained in the same manner as in Example 1, except that the formation of the coating layer was omitted. Comparative Example 3 A laminate of Comparative Example 3 was obtained in the same manner as in Comparative Example 2, except that Adhesive 3 was used instead of Adhesive 1. Comparative Example 4 A laminate of Comparative Example 4 was obtained in the same manner as in Example 2, except that Adhesive 3 was used instead of Adhesive 2.

[0149] <Evaluation> (Oxygen permeability) The obtained laminate was cut to a size of 10 cm x 10 cm, and the oxygen permeability was measured in accordance with JIS-K7126 (constant pressure method) using an OX-TRAN2 / 21 (oxygen permeability measuring device manufactured by Mocon) under atmospheres of 23°C, 0% RH, and 90% RH. RH indicates humidity.

[0150] (Oxygen permeability - after acceleration) The obtained laminate was cut into 12 cm x 30 cm. The long side of the film was folded in half, and two sides were heat-sealed at 180 ° C, 0.1 MPa, and 1 second, after which 5 g of contents was placed in, and the remaining side was heat-sealed under the same conditions to seal with a three-sided seal. At this time, a PET film was interposed between the laminate and the heat seal bar so that the laminate and the heat seal bar would not come into direct contact. After leaving this bag at 50 ° C for 4 weeks, it was opened and the contents were wiped off. A measurement sample of 10 cm x 10 cm was cut out from this, and the oxygen permeability was measured in the same manner as above. As the contents, Attack Antibacterial EX Super Clear Gel (Kao Corporation) and Merit Shampoo-DE1 (Kao Corporation) were used.

[0151] (Laminate strength) Using a tensile tester in an atmosphere of 25°C, the peel speed was set to 300 mm / min, and the adhesive strength (N / 15 mm) between the BOPE film and the LLDPE film was measured using a T-type peel method.

[0152] (Laminate strength - after acceleration) The obtained laminate was cut into 12 cm x 30 cm. The long side of the film was folded in half, and two sides were heat-sealed at 180 ° C, 0.1 MPa, and 1 second, after which 5 g of contents was placed in, and the remaining side was heat-sealed under the same conditions to seal with a three-sided seal. At this time, a PET film was interposed between the laminate and the heat seal bar so that the laminate and the heat seal bar would not come into direct contact. After leaving this bag at 50 ° C for 4 weeks, it was opened and the contents were wiped off. A measurement sample was cut out from this with a width of 15 mm, and the laminate strength was measured in the same manner as above. The contents used were Attack Antibacterial EX Super Clear Gel (manufactured by Kao Corporation) and Merit Shampoo-DE1 (Kao Corporation).

[0153] (Heat seal strength) The laminates produced in the examples and comparative examples were cut into 10 cm x 10 cm pieces, and the LLDPE films were placed facing each other and heat-sealed using a heat sealer at 180°C, 0.1 MPa, and 1 second to heat-seal the LLDPE films. At this time, a PET film was placed between the laminate and the heat seal bar so that the laminate and the heat seal bar would not come into direct contact with each other. Both ends of a sample cut out to a width of 15 mm from this were fixed to a tensile tester and measured in tensile mode (tensile speed: 300 mm / min). Five measurements were taken under the same measurement conditions, and the average was taken as the heat seal strength. The unit is N / 15 mm.

[0154] (Heat seal strength - after acceleration) The obtained laminate was cut into 12 cm x 30 cm. The long side of the film was folded in half, and two sides were heat-sealed at 180°C, 0.1 MPa, and 1 second, after which 5 g of contents was placed in the film, and the remaining side was heat-sealed under the same conditions to seal the film in a three-sided seal mold. At this time, a PET film was placed between the laminate and the heat seal bar so that they would not come into direct contact with each other. After leaving the bag at 50°C for 4 weeks, it was opened and the contents were wiped off. The heat-sealed portion was cut out to a width of 15 mm, and both ends of the sample were fixed to a tensile tester and measured in tensile mode (tensile speed: 300 mm / min). Five measurements were taken under the same measurement conditions, and the average was taken as the heat seal strength. The unit is N / 15 mm. The contents used were Attack Antibacterial EX Super Clear Gel (Kao Corporation) and Merit Shampoo-DE1 (Kao Corporation).

[0155] (fragrance retention) The obtained laminate was cut into 7 cm x 16 cm. The long side of the film was folded in half, and two sides were heat-sealed at 160°C for 1 second, after which 5 g of contents was placed in the bag, and the remaining side was heat-sealed to seal the bag in a three-sided seal. The bag was immediately placed in a mayonnaise bottle (M-70) manufactured by Kakuyo Glass Co., Ltd., and sealed, and stored for three days at a temperature of 40°C and a relative humidity of 60%. A sensory evaluation was performed by four panelists on a five-point scale, and the average evaluation results of each panelist are summarized in Tables 1 and 2. The closer to 1, the less odor there was and the laminate had excellent aroma retention, and the closer to 5, the stronger the odor. The contents used were Attack Antibacterial EX Super Clear Gel (manufactured by Kao Corporation) and Merit Shampoo-DE1 (Kao Corporation).

[0156] [Table 1]

Claims

1. A stretched polyethylene film; An ethylene-based heat seal layer having a thickness of 45 μm to 250 μm; a coating layer disposed between the stretched polyethylene film and the ethylene-based heat seal layer; an adhesive layer disposed between the stretched polyethylene film and the ethylene-based heat seal layer and adjacent to the ethylene-based heat seal layer; It does not include an inorganic vapor deposition layer, or a coating layer having gas barrier properties which is a dried coating film of a coating agent containing a resin having gas barrier properties and an aqueous solvent, the coating layer is a cured coating film of a coating agent containing a polyester polyol having a skeleton derived from an ortho-oriented aromatic carboxylic acid and a polyisocyanate, The adhesive layer is a cured coating film of an adhesive containing a polyester polyol having a skeleton derived from an ortho-oriented aromatic carboxylic acid and a polyisocyanate.

2. 2. The liquid packaging laminate according to claim 1, further comprising a heat-resistant coating layer on the surface of said stretched polyethylene film opposite to said coating layer.

3. 2. The laminate for liquid packaging according to claim 1, wherein the adhesive is a solvent-free adhesive.

4. The laminate for liquid packaging according to claim 1 , further comprising a print layer.

5. The laminate for liquid packaging according to claim 1, wherein the coating agent contains a drying aid.

6. The laminate for liquid packaging according to claim 1, wherein the coating agent contains an anti-skinning agent.

7. A liquid packaging material obtained by forming a bag from the laminate according to any one of claims 1 to 6.

8. A front member, a back member, and a bottom member are included. The front member, the rear member, and the bottom member are the laminate according to any one of claims 1 to 6, The front member and the back member are overlapped and the left and right side edge portions are heat-sealed, The front member and the bottom member are heat-sealed, The liquid packaging material has the back member and the bottom member heat-sealed together.

9. 9. The liquid packaging material according to claim 8, wherein the front member, the rear member and the bottom member are laminated bodies having the same structure.

10. 9. The liquid packaging material according to claim 8, wherein the front member, the rear member and the bottom member are laminated bodies having different configurations.

Citation Information

Patent Citations

  • Low-elution packaging material

    JP2004238050A

  • Laminate and method for manufacturing laminate

    JP2014004799A

  • Coated film and packages formed therefrom

    JP2018522757A

  • Coated films and articles formed therefrom

    JP2019530594A

  • Laminate, packaging material, packaging bag and stand pouch

    JP2020055156A